A simulator providing theoretical research of human integrative physiology - Grygoryan, R.D.; Sinitsin, I.P.; Degoda, A.G.; Lyudovyk, T.V.; Yurchak, O.I. (PROBLEMS IN PROGRAMMING, 2026)
Traditional (empiric) methodology based on direct measurements of fragmentary biological data limits the research of human integrative physiology (IP). Even assistant research based on animal experiments operates with fragmentary data. Therefore, IP’s current concepts, not covering many aspects of IP’s complex dynamics, cannot explain pathophysiological transformations that finally lead to non-trivial diseases. This methodological dead-end requires alternative research technology. This article presents a technology and software (SimHIP), widening the research potential in the area of human IP. The technology is based on two novelties. The first one is the physiological concept of a functional super-system (FSS) that optimizes cells' life despite environmental instabilities. The second novelty is the mathematical model (MM) of FSS. Fragments of MM were separately created and tuned using test scenarios. SimHIP integrating these fragments provides the physiologist-researcher with an intuitive interface to: a) construct a simulation scenario; b) execute the simulation; c) visualize input-output physiological dynamic dependencies for every chosen combination; and d) save every simulation data for future considerations and publications. SimHIP is an autonomous C# software provided as an Exe module for IBM-compatible computers. Medical students can be additional users of SimHIP.Problems in programming 2025; 4: 12-22